Measurements of muon beam properties in MICE - Rayner, M; Cobb, J (2010)
The Muon Ionization Cooling Experiment is one lattice section of a cooling channel suitable for conditioning the muon beam at the front end of a Neutrino Factory or Muon Collider. Scintillating fibre spectrometers and timing detectors provide a measurement of the six-dimensional phase space vectors of individual muons before and after cooling. Simulations based on measurements of the real muon beam show that it is well matched to the requirements of MICE.